Podocalyxin Is a Marker of Poor Prognosis in Pancreatic Ductal Adenocarcinoma - Saukkonen, Kapo (PLoS One, 2015)
AIM OF THE STUDY: Podocalyxin-like 1 is a transmembrane glyco-protein whose overexpression associates in many cancers with poor prognosis and unfavorable clinicopathological characteristics. Until now, its prognostic value has never been studied in pancreatic ductal adenocarcinoma (PDAC). The aim of this study was to investigate podocalyxin expression in PDAC by a novel monoclonal antibody and a commercially available polyclonal antibody. PATIENTS AND MATERIALS: With tissue microarrays and immuno-histochemistry, podocalyxin expression evaluation involved 168 PDAC patients. The associa-tions of the podocalyxin tumor expression with clinicopathological variables were explored by Fisher’s exact test and the linear-by-linear test. Survival analyses were by Kaplan-Meier anal-ysis and the Cox proportional hazard model. RESULTS: The polyclonal antibody revealed membranous podocalyxin expression in 73 (44.0%) specimens and the monoclonal antibody was highly expressed in 36 (21.8%) cases. Membranous expression by the polyclonal antibody was associated with T classification (p=0.045) and perineural invasion (p=0.005), and high expression by the mono-clonal antibody with poor differentiation (p=0.033). High podocalyxin expression associated significantly with higher risk of death from PDAC by both the polyclonal antibody (hazard ratio (HR) = 1.62; 95% confidence interval (CI) 1.12-2.33; p=0.01) and the monoclonal antibody (HR = 2.10, 95% CI 1.38-3.20; p<0.001). The results remained significant in multivariate analysis, adjusted for age, gender, stage, lymph node ratio (≥/< 20%), and perivascular invasion (respectively as HR = 2.03; 95% CI 1.32-3.13, p=0.001; and as HR = 2.36; 95% CI 1.47-3.80, p<0.001). CONCLUSION: We found podocalyxin to be an independent factor for poor prognosis in PDAC. To our knowledge, this is the first such report of its prognostic value.